NF-κB, I-κB and IRAK Control Glutamate Receptor Density at the Drosophila NMJ - Heckscher, Elizabeth S. (2007)
NF-κB signaling has been implicated in neurodegenerative disease, epilepsy, and neuronal plasticity. However, the cellular and molecular activity of NF-κB signaling within the nervous system remains to be clearly defined. Here we show that the NF-κB and IκB homologues Dorsal and Cactus surround postsynaptic glutamate receptor (GluR) clusters at the Drosophila NMJ. We then show that mutations in dorsal, cactus and IRAK/pelle kinase specifically impair GluR levels, assayed immunohistochemically and electrophysiologically, without affecting NMJ growth, the size of the postsynaptic density, or homeostatic plasticity. Additional genetic experiments support the conclusion that cactus functions in concert with, rather than in opposition to, dorsal and pelle in this process. Finally, we provide evidence that Dorsal and Cactus act post-transcriptionally, outside the nucleus, to control GluR density. Based upon our data we speculate that Dorsal, Cactus and Pelle could function together, locally at postsynaptic density, to specify GluR levels.